The Impact of Moderating Effect of Coaching on the Association Between Workplace Training and The Distribution of Training Results - Stefano de Nichilo (Majapahit Journal of Islamic Finance and Management, 2023)
In recent years, coaching has been a prominent method for developing employees, with various objectives such as boosting professional skills, promoting student learning outcomes, and strengthening the effectiveness of training programmes within businesses. The existing literature on the subject is somewhat scarce, as it pertains to the investigation of coaching's influence on the effectiveness of training. Therefore, the primary objective of this study is to investigate the impact of in-class training on the execution of training outcomes, with a specific focus on project assignments. Furthermore, the primary objective of this study is to examine the potential moderating role of coaching in the association between in-class training and the realisation of training outcomes, specifically in the context of project assignments. The main methodology applied in this study is a quantitative approach, in which numerical data is utilised and submitted for quantitative analysis. The research data was obtained from the results of the assessment of the MDP training curriculum. The study sample comprised 131 individuals. The methodology utilised in this study for data processing is Moderate Regression Analysis (MRA). The results of the study utilising Multiple Regression Analysis (MRA) suggest that coaching acts as a moderating variable in the Quasi model. Research has demonstrated that training is effective in enhancing an individual's knowledge, equipping them with the analytical skills necessary for identifying and resolving issues within their respective work units. The implementation of this approach facilitates the coaching process, enhancing its efficiency and concentration, hence leading to the successful completion of performance appraisals. This suggests that the integration of coaching with Class Training results in an observed improvement in the ability to carry out Project Assignments (PA) with greater effectiveness. The ability to fulfil project activities includes the proficiency to produce project evaluation reports and deliver presentations.